Aluminum matrix composite and high-throughput method of preparation

CN118389890BActive Publication Date: 2026-10-23INST OF METAL RESEARCH - CHINESE ACAD OF SCI +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410631618.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-21
Publication Date
2026-10-23
Estimated Expiration
2044-05-21

AI Technical Summary

Benefits of technology

[0026]一方面,本发明实施例提供一种铝基复合材料的高通量制备方法,其包括如下步骤:准备多种不同类型的原料粉末;其中,每一种类型的原料粉末均包括铝基体粉末和增强相;准备具有多个容置腔的蜂窝状结构;将不同类型的原料粉末一一对应地分别装填到不同的容置腔内,得到装有不同类型原料粉末的蜂窝状结构;对所述装有不同类型原料粉末的蜂窝状结构进行冷压成型,得到蜂窝状坯块;对所述蜂窝状坯块进行真空热压处理,得到蜂窝状坯锭;对所述蜂窝状坯锭进行热挤出处理,得到蜂窝状挤出结构;对所述蜂窝状挤出结构进行热处理,得到蜂窝状铝基复合材料;其中,所述蜂窝状铝基复合材料包括多种类型的铝基复合材料单元;不同的铝基复合材料单元之间通过蜂窝状结构相互隔离。在此,关于上述步骤需要说明的是:本发明利用蜂窝状结构,并结合上述步骤,能够在单次实验内制备出的铝基复合材料包括多种类型的铝基复合材料单元,这些单元彼此隔开,从而能实现增强相体积分数、种类及基体种类间相互作用的同步研究,同时,最大程度减小了制备工艺误差、装置稳定性对于铝基复合材料的影响,有利于快速确定所需性能的铝基复合材料的最佳增强相种类、体积分数及铝基体,并实现铝基复合材料的批量生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118389890B_ABST
    Figure CN118389890B_ABST
Patent Text Reader

Abstract

The application relates to an aluminum-based composite material and a high-throughput preparation method, wherein the high-throughput preparation method comprises the following steps: preparing a plurality of different types of raw material powders; preparing a honeycomb structure with a plurality of accommodation cavities; filling the different types of raw material powders into the different accommodation cavities one by one and respectively, so as to obtain a honeycomb structure filled with different types of raw material powders; cold-pressing the honeycomb structure filled with different types of raw material powders, so as to obtain a honeycomb blank; performing vacuum hot-pressing treatment on the honeycomb blank, so as to obtain a honeycomb blank ingot; performing hot extrusion treatment on the honeycomb blank ingot, so as to obtain a honeycomb extrusion structure; and performing heat treatment on the honeycomb extrusion structure, so as to obtain a honeycomb aluminum-based composite material; wherein the honeycomb aluminum-based composite material comprises a plurality of types of aluminum-based composite material units. The application can prepare a plurality of aluminum-based composite materials at one time, and the prepared materials can be subjected to high-throughput characterization subsequently.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aluminum-based composite materials technology, and in particular to an aluminum-based composite material and a high-throughput preparation method. Background Technology

[0002] In recent years, metal matrix composites have gradually become a research focus due to their superior mechanical strength and excellent wear resistance. Currently, the most widely used matrix materials mainly include aluminum, magnesium, and titanium. As the third most abundant element in the Earth's crust, aluminum is widely used in aerospace, automotive, and electronics fields due to its advantages such as lightweight, high strength, ease of processing and forming. With the vigorous development of my country's aerospace industry, higher requirements have been placed on material performance, thus creating development opportunities for aluminum matrix composites. Aluminum matrix composites use aluminum and its alloys as the matrix, with ceramics, metals, or organic compounds added as reinforcing phases. They retain the advantages of the aluminum matrix and its alloys while improving performance through the addition of reinforcing phases, exhibiting excellent properties such as high specific strength, high specific stiffness, low density, wear resistance, and corrosion resistance.

[0003] In aluminum matrix composites, ceramic particles, whiskers, and fibers are three common types of reinforcing phases. Particle-reinforced aluminum matrix composites are widely used due to their advantages such as low coefficient of friction, excellent high-temperature mechanical properties, and low cost. Common particle reinforcements include silicon carbide particles (SiCp), titanium carbide particles (TiC), alumina particles (Al2O3), zirconium oxide particles (ZrO2), and silica particles (SiO2). Whiskers refer to single crystals with a diameter in the micrometer or submicrometer range and an aspect ratio greater than 10. They are an excellent type of reinforcement due to their high strength, high elastic modulus, stable chemical properties, and strong wear resistance. Aluminum matrix composites reinforced with silicon carbide whiskers (SiCw), titanium boride whiskers (TiB2), and zirconium boride whiskers (ZrB2) have achieved relatively widespread application. While carbon fiber (Cf) and carbon nanotubes (CNTs) exhibit excellent performance, their high cost limits their development and application, although they hold significant research potential in the aerospace field.

[0004] Traditional methods for preparing and developing aluminum-based composite materials involve conducting experiments on each factor individually to address their influence. This approach is time-consuming, costly, and susceptible to unforeseen complications from different batches, failing to meet the growing demands of the manufacturing industry. One related technology discloses a method for preparing graphene-based aluminum-based composite materials. This method involves multiple experiments to prepare aluminum-based composite materials and control samples, but it doesn't account for external interference from different batches and is relatively expensive. Another related technology discloses a method for preparing nano-titanium carbide-reinforced 2024 aluminum-based composite materials. This method involves multiple experiments to prepare aluminum-based composite materials for performance comparison, but it is not only costly but also susceptible to external interference. Therefore, the Materials Genome Initiative has opened up new avenues for materials research and manufacturing, aiming to double the efficiency of materials research and halve research costs. High-throughput preparation is one of the three pillars of materials genome engineering.

[0005] In summary, there is an urgent need for a high-throughput preparation method for aluminum-based composite materials that can prepare multiple aluminum-based composite materials at once and subsequently perform high-throughput characterization of the prepared materials. Summary of the Invention

[0006] In view of this, the present invention provides an aluminum-based composite material and a high-throughput preparation method, the main purpose of which is to prepare multiple aluminum-based composite materials in one step, and to perform high-throughput characterization of the prepared materials in the subsequent process.

[0007] To achieve the above objectives, the present invention mainly provides the following technical solutions:

[0008] On one hand, embodiments of the present invention provide a high-throughput preparation method for aluminum-based composite materials, which includes the following steps:

[0009] Raw material preparation: Prepare various types of raw material powders; each type of raw material powder includes aluminum matrix powder and reinforcing phase;

[0010] Prepare a honeycomb structure: Prepare a honeycomb structure with multiple cavities; fill different types of raw material powders into different cavities one by one to obtain honeycomb structures filled with different types of raw material powders;

[0011] Cold pressing: The honeycomb structure containing different types of raw material powder is cold pressed to obtain a honeycomb blank;

[0012] Hot pressing: The honeycomb-shaped billet is subjected to vacuum hot pressing to obtain a honeycomb-shaped ingot;

[0013] Hot extrusion treatment: The honeycomb billet is subjected to hot extrusion treatment to obtain a honeycomb extruded structure;

[0014] Heat treatment: The honeycomb extrusion structure is heat treated to obtain a honeycomb aluminum-based composite material; wherein, the honeycomb aluminum-based composite material includes various types of aluminum-based composite material units, and different aluminum-based composite material units are isolated from each other by a honeycomb structure.

[0015] Preferably, in the step of preparing raw materials: the aluminum matrix powder is selected from aluminum powder or aluminum alloy powder; and / or the reinforcing phase is selected from ceramic phase and / or carbon material; preferably, the reinforcing phase is selected from one or more of alumina, silicon carbide, boron carbide, and carbon nanotubes.

[0016] Preferably, in the step of preparing the raw materials: in each type of raw material powder, the content of the reinforcing phase is 0-50 vol%, preferably 0.5-30 vol%.

[0017] Preferably, in the step of preparing raw materials: when preparing each type of raw material powder, aluminum matrix powder and reinforcing phase are placed in a ball mill and ball milled under an inert atmosphere; preferably, the ball milling speed is 100-400 rpm, the ball-to-powder ratio is (5-15):1, and the ball milling time is 5-15 h; preferably, stearic acid needs to be added during the ball milling process to prevent the raw material powder from sintering.

[0018] Preferably, in the step of preparing the honeycomb structure: the honeycomb structure is a hexagonal honeycomb structure; and / or the material of the honeycomb structure is aluminum.

[0019] Preferably, the two ends of the accommodating cavities on the honeycomb structure are open. Preferably, a mold for cold pressing and hot pressing is prepared, a first graphite block is placed at the bottom of the mold, the honeycomb structure is placed on the graphite block, and then different types of raw material powders are filled into different accommodating cavities one by one. The mold is sealed with a second graphite block, and then cold pressing and hot pressing are performed sequentially. Preferably, before placing the honeycomb structure into the mold, silicon carbide needs to be brushed onto the inner wall of the mold (here, brushing with silicon carbide is to facilitate the subsequent demolding of the honeycomb ingot after hot pressing; otherwise, the honeycomb ingot and the mold will stick together, and demolding will damage the honeycomb ingot). Preferably, after hot pressing, the mold and graphite block are removed.

[0020] Preferably, in the cold pressing step, the pressure of the cold press is set to 3-5t, and the holding time is 5-30s.

[0021] Preferably, in the hot pressing step: in a vacuum hot press furnace, the stearic acid in the honeycomb blank is first removed by heating, and then hot pressing is performed. After the hot pressing is completed, the furnace is cooled down. Preferably, the temperature for removing stearic acid from the honeycomb blank is 673-723K, and the holding time is 1-2h. Preferably, the temperature for hot pressing is 813-903K. After holding at the hot pressing temperature for 1-2h, the pressure is increased to 15-20t, and the temperature and pressure are maintained for 30-60min.

[0022] Preferably, in the hot extrusion step: an Al alloy block is welded to one end of a honeycomb billet, and then the honeycomb billet is hot-extruded in the direction of hot pressing to extrude the honeycomb billet into a honeycomb extruded structure; preferably, the Al alloy block is a 6061Al alloy block and / or the honeycomb extruded structure is a rod; and / or, the hot extrusion temperature is 723-823K and the extrusion ratio is (4-16):1.

[0023] Preferably, in the heat treatment step: the honeycomb extruded structure is subjected to solution treatment, quenching, and natural aging in sequence to obtain a honeycomb aluminum-based composite material; preferably, the solution treatment temperature is 723-873K and the time is 2-5h; preferably, the quenching is carried out in water; preferably, the natural aging time is more than 96h.

[0024] In another aspect, embodiments of the present invention provide a honeycomb aluminum-based composite material, wherein the honeycomb aluminum-based composite material includes various types of aluminum-based composite material units and a honeycomb structure; different aluminum-based composite material units are isolated from each other by the honeycomb structure; preferably, the aluminum-based composite material is prepared by the preparation method of the aluminum-based composite material described in any one of the above claims.

[0025] Compared with the prior art, the aluminum-based composite material and its high-throughput preparation method of the present invention have at least the following beneficial effects:

[0026] On one hand, embodiments of the present invention provide a high-throughput preparation method for aluminum-based composite materials, comprising the following steps: preparing multiple different types of raw material powders; wherein each type of raw material powder includes aluminum matrix powder and a reinforcing phase; preparing a honeycomb structure having multiple cavities; filling different types of raw material powders into different cavities one by one to obtain honeycomb structures containing different types of raw material powders; cold-pressing the honeycomb structures containing different types of raw material powders to obtain honeycomb blanks; vacuum hot-pressing the honeycomb blanks to obtain honeycomb ingots; hot-extruding the honeycomb ingots to obtain honeycomb extruded structures; heat-treating the honeycomb extruded structures to obtain honeycomb aluminum-based composite materials; wherein the honeycomb aluminum-based composite materials include multiple types of aluminum-based composite material units; different aluminum-based composite material units are isolated from each other by the honeycomb structure. Here, it should be noted that the present invention utilizes a honeycomb structure and, in conjunction with the above steps, can prepare aluminum-based composite materials including multiple types of aluminum-based composite material units in a single experiment. These units are separated from each other, thereby enabling simultaneous research on the volume fraction and type of reinforcing phase and the interaction between matrix types. At the same time, it minimizes the impact of preparation process errors and device stability on aluminum-based composite materials, which is beneficial for quickly determining the optimal type, volume fraction, and aluminum matrix of aluminum-based composite materials with the required properties, and realizing the mass production of aluminum-based composite materials.

[0027] Furthermore, the high-throughput preparation method of aluminum-based composite materials proposed in this embodiment of the invention uses a hexagonal honeycomb structure. This hexagonal honeycomb structure serves as a framework, which deforms in coordination with the material throughout the entire preparation process without being destroyed, thus avoiding mixing and contamination of adjacent aluminum-based composite materials and playing an isolation role.

[0028] Furthermore, the high-throughput preparation method for aluminum-based composite materials proposed in this invention includes hot pressing and hot extrusion processes. The hot extrusion step offers advantages in improving production efficiency, reducing material defects, and enhancing mechanical properties throughout the entire preparation process. Simultaneously, the hot extrusion and hot pressing steps have a synergistic effect. During hot pressing, the material undergoes high temperature and pressure, causing powder particles to diffuse and bond between particles, forming a preliminary dense structure. The hot extrusion process further compacts and plastically deforms the material, increasing its density, reducing defects, and enhancing grain boundary bonding, thereby improving the material's strength, hardness, and wear resistance.

[0029] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described in detail below with reference to the accompanying drawings. Attached Figure Description

[0030] Figure 1 This is a picture of a hexagonal aluminum honeycomb structure.

[0031] Figure 2 This is a schematic diagram of the aluminum-based composite material prepared in Example 1;

[0032] Figure 3 This is a photograph of the honeycomb ingot prepared in Example 1;

[0033] Figure 4 This is a photograph of the honeycomb rod material prepared in Example 1;

[0034] Figure 5 This is a microstructure diagram of the aluminum-based composite material prepared in Example 1;

[0035] Figure 6 This is a microstructure diagram of the aluminum-based composite material prepared in Example 2;

[0036] Figure 7 This is a microstructure diagram of the honeycomb aluminum-based composite material obtained in Comparative Example 1. Detailed Implementation

[0037] To further illustrate the technical means and effects adopted by the present invention to achieve the intended purpose, the specific embodiments, structures, features, and effects according to the present invention will be described in detail below with reference to the accompanying drawings and preferred embodiments. In the following description, different "an embodiment" or "an embodiment" do not necessarily refer to the same embodiment. Furthermore, specific features, structures, or characteristics in one or more embodiments can be combined in any suitable form.

[0038] To address the low research and material preparation efficiency of existing aluminum-based composite material research and preparation processes, this invention proposes an aluminum-based composite material and its high-throughput preparation method. This high-throughput preparation method can prepare multiple different types of aluminum-based composite materials in a single process. Subsequent high-throughput characterization of the prepared materials is also possible, such as using micro-area electron diffraction (μ-XRD) to analyze phase composition, micro-area X-ray fluorescence spectroscopy (μ-XRF) to analyze elemental distribution, and using scanning electron microscopy (SEM), backscattered electron diffraction (EBSD), and energy dispersive spectroscopy (EDS) to analyze the microstructure and composition of the composite material.

[0039] The specific solution of the present invention is as follows:

[0040] On one hand, embodiments of the present invention provide a high-throughput preparation method for aluminum-based composite materials, mainly including the following steps:

[0041] Raw material preparation: Prepare various types of raw material powders; each type of raw material powder includes aluminum matrix powder and reinforcing phase.

[0042] The different types here include one or more differences in the type of aluminum matrix, the type of reinforcing phase, and the content of the reinforcing phase in the raw material powder.

[0043] In this step: First, design the required types of aluminum-based composite materials: pre-design the required raw material powders, screen the aluminum matrix powders of the aluminum-based composite materials, and determine the types and contents of the reinforcing phases.

[0044] In preparing each type of raw material powder, the screened aluminum matrix powder and reinforcing phase are placed in a high-energy ball mill and then ball-milled under argon conditions to obtain the raw material powder.

[0045] The ball milling process involves a rotation speed of 100-400 rpm, a ball-to-powder ratio of (5-15):1, and a milling time of 5-15 hours. Preferably, the ball milling speed is 250 rpm, the ball-to-powder ratio is 15:1, and the milling time is 10 hours. Stearic acid needs to be added during ball milling to prevent powder sintering.

[0046] In the raw material powder: the content of the reinforcing phase is 0-50 vol%, preferably 0.5-30 vol%.

[0047] Prepare a honeycomb structure: Prepare a honeycomb structure with multiple cavities; fill different types of raw material powders into different cavities one by one to obtain honeycomb structures containing different types of raw material powders.

[0048] Preferably, in the step of preparing the honeycomb structure: the honeycomb structure is a hexagonal honeycomb structure.

[0049] Preferably, the honeycomb structure is made of aluminum.

[0050] Preferably, the accommodating cavity on the honeycomb structure is open at both ends.

[0051] Preferably, a mold for cold pressing and hot pressing is prepared. A first graphite block is placed at the bottom of the mold, and the honeycomb structure is placed on the graphite block. Then, different types of raw material powders are filled into different cavities one by one. The mold is sealed with a second graphite block, and then cold pressing and hot pressing are performed sequentially. Preferably, silicon carbide is brushed onto the inner wall of the mold before placing the honeycomb structure into the mold. Preferably, the mold and graphite block are removed after hot pressing. Preferably, the diameter of the graphite block is 1-2 mm larger than the mold cavity, and the thickness is 20 mm.

[0052] Cold pressing: The honeycomb structure containing different types of raw material powder is cold pressed to obtain a honeycomb blank.

[0053] In this step, the pressure of the cold press is 3-5t (preferably 5t), and the pressure holding time is 5-30s (preferably 30s).

[0054] Hot pressing: The honeycomb-shaped billet is subjected to vacuum hot pressing to obtain a honeycomb-shaped ingot.

[0055] In this step, the mold containing the honeycomb-shaped blank is placed into a vacuum hot press furnace. First, the temperature is raised to remove stearic acid from the powder, followed by hot pressing. After hot pressing, the furnace is cooled. Preferably, the temperature for removing stearic acid from the powder is 673-723K (preferably 673K), and the holding time is 1-2 hours (preferably 1 hour). More preferably, the hot pressing temperature is 813-903K (preferably 813K). After holding at the hot pressing temperature for 1-2 hours (preferably 1 hour), the pressure is increased to 15-20t (preferably 20t), and the holding time is 30-60 minutes (preferably 30 minutes) before cooling. After hot pressing, the mold and graphite block are removed.

[0056] Hot extrusion treatment: The honeycomb ingot is subjected to hot extrusion treatment to obtain a honeycomb extruded structure.

[0057] In this step, a 6061Al alloy block is welded to one end of a honeycomb ingot. The ingot is then hot-extruded into a bar along the hot-pressing direction. The hot extrusion temperature is 723-823K, and the extrusion ratio is (4-16):1.

[0058] Here, the thickness of the 6061Al alloy block is 12-13 mm, which is 2-3 mm thinner than the thickness of the honeycomb ingot. It should be noted that the 6061Al alloy has good plasticity, allowing for adjustment of the hot-pressing stress through plastic deformation, resulting in a more uniform pressure distribution and better material properties after extrusion. It also reduces die wear, lowers the required extrusion pressure, and prevents deformation of the extrusion rod and cylinder due to excessive stress.

[0059] Heat treatment: The honeycomb extruded structure is heat-treated to obtain a honeycomb aluminum-based composite material; wherein, the honeycomb aluminum-based composite material includes various types of aluminum-based composite material units. Different aluminum-based composite material units are isolated from each other by the honeycomb structure.

[0060] In this step, the honeycomb extruded structure is subjected to solution treatment, quenching, and natural aging in sequence to obtain a honeycomb aluminum-based composite material; preferably, the solution treatment temperature is 723-873K (preferably 773K) and the time is 2-5h (preferably 2h); preferably, the quenching is carried out in water; preferably, the natural aging time is more than 96h.

[0061] Here, it should be noted that the above-mentioned solution of the present invention is as follows:

[0062] 1. This invention can simultaneously study the volume fraction and type of reinforcing phase and the interaction between matrix types in a single experiment, minimizing the impact of preparation process errors and device stability on aluminum matrix composites. It is beneficial to quickly determine the optimal reinforcing phase type, volume fraction and aluminum matrix of aluminum matrix composites with the required properties, and realize the mass production of aluminum matrix composites.

[0063] 2. The hexagonal aluminum honeycomb frame (i.e., honeycomb structure) in this invention can deform in coordination with the material without being destroyed, avoiding mixing and contamination of adjacent aluminum-based composite materials, and playing an isolation role.

[0064] The present invention will be further illustrated below with specific embodiments:

[0065] Example 1

[0066] This embodiment provides a high-throughput preparation method for aluminum-based composite materials, which can prepare multiple aluminum-based composite materials in one step, and subsequently perform high-throughput characterization on the prepared materials. Details are as follows:

[0067] 1) Design of Aluminum-Based Composite Materials: The aluminum matrix for the aluminum-based composite materials to be screened includes pure aluminum, 2009Al (i.e., aluminum alloy of type 2009Al), 2024Al (i.e., aluminum alloy of type 2024Al), and 2219Al (i.e., aluminum alloy of type 2219Al). The reinforcing phases include Al2O3, TiC, B4C, and CNTs, with a reinforcing phase content of 1-6 vol%, in 1 vol% increments. For simplicity, the designed aluminum-based composite material is represented as A+B(C). Here, A represents the matrix type, B represents the reinforcing type, and C represents the reinforcing phase content (vol%). Specifically, the type of aluminum-based composite material designed in this embodiment (the aluminum-based composite material to be prepared) is as follows:

[0068] Al+SiC (1vol%), Al+SiC (2vol%), Al+SiC (3vol%), Al+SiC (4vol%), Al+SiC (5vol%), 2009Al+Al2O3 (1vol%), 2009Al+A l2O3 (2vol%), 2009Al+Al2O3 (3vol%), 2009Al+Al2O3 (4vol%), 2009Al+Al2O3 (5vol%), 2009Al+Al2O3 (6vol%), 2024Al+ B4C (1vol%), 2024Al+B4C (2vol%), 2024Al+B4C (3vol%), 2024Al+B4C (4vol%), 2024Al+B4C (5vol%), 2219Al+CNTs (1vo 1%), 2219Al+CNTs (2vol%), 2219Al+CNTs (3vol%), 2219Al+CNTs (4vol%), 2219Al+CNTs (5vol%), 2219Al+CNTs (6vol%).

[0069] The required raw materials are as follows: Al2O3 powder with an average particle size of 10 μm; SiC powder with an average particle size of 10 μm; B4C powder with an average particle size of 10 μm; CNTs with an average particle size of 10 nm and a length of approximately 5 μm; pure aluminum powder with an average particle size of 180 μm; 2009Al powder with an average particle size of 10 μm; 2024Al powder with an average particle size of 63.4 μm; and 2219Al powder with an average particle size of 26.6 μm.

[0070] To prepare various types of aluminum-based composite materials, multiple types of raw material powders were generated. The corresponding matrix phase powder and reinforcing phase powder for each type were mixed and ball-milled to obtain the corresponding raw material powder. The ball milling speed was 250 rpm, the ball-to-powder ratio was 15:1, and the milling time was 10 hours.

[0071] 2) Brush silicon carbide onto the inner wall of the prepared mold, and then... Figure 1 The hexagonal aluminum honeycomb structure shown is placed in the mold, and then the different types of raw material powder prepared in step 1) are filled into the different cavities one by one to obtain honeycomb structures filled with different types of raw material powder. Take a graphite block with a diameter 1-2 mm larger than the mold cavity and a thickness of 20 mm, and place it on both sides of the mold.

[0072] 3) At room temperature, cold pressing is performed. A cold press is used to press the graphite block into the mold cavity at a pressure of 5t for 30s. The honeycomb structure containing different types of raw material powder is cold pressed to form a honeycomb blank.

[0073] 4) Place the mold containing the honeycomb ingot into a vacuum hot press furnace. First, heat to 673K ​​and hold for 1.5 hours to remove stearic acid. Then, heat to 813K and hold for 1 hour, followed by hot pressing until dense. After the pressure is increased to 20t, hold at that temperature for 30 minutes, and then cool down with the furnace. After removing the mold, the honeycomb ingot is obtained.

[0074] 5) Take a 6061Al block with a thickness of 12-13mm and a diameter 2-3mm smaller than the honeycomb ingot. Weld the 6061Al block to one end of the honeycomb ingot. Hot-extrude the honeycomb ingot into honeycomb rods at 723K along the hot-pressing direction with an extrusion ratio of 16:1.

[0075] 6) The bar is solution treated at 773K for 2 hours, then quenched in water and aged naturally for more than 96 hours to obtain a honeycomb aluminum matrix composite material; wherein, the honeycomb aluminum matrix composite material includes various types of aluminum matrix composite material units, and the aluminum matrix composite material units correspond one-to-one with the honeycomb units.

[0076] A schematic diagram of the honeycomb aluminum-based composite material obtained in this embodiment is shown below. Figure 2 As shown.

[0077] Figure 3 This is a photograph of the honeycomb ingot prepared in this embodiment. Here, the ends are slightly blurred due to the cold and hot pressing processes; after rubbing them, the honeycomb cells can be cleaned and seen.

[0078] Figure 4 A photograph of the cut honeycomb rod material prepared in this embodiment, from... Figure 4 The honeycomb structure at the end of the rod can be seen.

[0079] Figure 5 This is a microstructure diagram of the honeycomb aluminum-based composite material prepared in this embodiment; the light colors represent hexagonal aluminum honeycomb structures, and the dark colors represent different aluminum-based composite material units. Figure 5 As can be seen, the hexagonal aluminum honeycomb structure remains intact and undamaged. The honeycomb structure effectively separates different types of aluminum-based composite materials.

[0080] Example 2

[0081] This embodiment provides a high-throughput preparation method for aluminum-based composite materials, which can prepare multiple aluminum-based composite materials in one step, and subsequently perform high-throughput characterization on the prepared materials. Details are as follows:

[0082] 1) Design of Aluminum-Based Composite Materials: The aluminum matrix for the aluminum-based composite materials to be screened includes pure aluminum, 5052Al (aluminum alloy of type 5052Al), 5056Al (aluminum alloy of type 5056Al), 6063Al (aluminum alloy of type 6063Al), and 7075Al (aluminum alloy of type 7075Al). The reinforcing phases include Al2O3, TiC, B4C, and CNTs, with a reinforcing phase content of 1-6 vol%, in 1 vol% increments. For simplicity, the designed aluminum-based composite material is represented as A+B(C). Here, A represents the matrix type, B represents the reinforcing type, and C represents the reinforcing phase content (vol%). Specifically, the type of aluminum-based composite material designed in this embodiment (the aluminum-based composite material to be prepared) is as follows:

[0083] 5052Al+SiC (1vol%), 5052Al+SiC (2vol%), 5052Al+SiC (3vol%), 5052Al+SiC (4vol%), 5052Al+SiC (5vol%), 5056Al+Al2O3 ( 1vol%), 5056Al+Al2O3 (2vol%), 5056Al+Al2O3 (3vol%), 5056Al+Al2O3 (4vol%), 5056Al+Al2O3 (5vol%), 5056Al+Al2O3 (6vol %), 6063Al+B4C (1vol%), 6063Al+B4C (2vol%), 6063Al+B4C (3vol%), 6063Al+B4C (4vol%), 6063Al+B4C (5vol%), 7075Al+CNT s(1vol%), 7075Al+CNTs(2vol%), 7075Al+CNTs(3vol%), 7075Al+CNTs(4vol%), 7075Al+CNTs(5vol%), 7075Al+CNTs(6vol%).

[0084] The required raw materials are as follows: Al2O3 powder with an average particle size of 10 μm; SiC powder with an average particle size of 10 μm; B4C powder with an average particle size of 10 μm; CNTs with an average particle size of 10 nm and a length of approximately 5 μm; 5052Al with an average particle size of 10 μm; 5056Al powder with an average particle size of 10 μm; 6063Al powder with an average particle size of 80 μm; and 7075Al powder with an average particle size of 79.5 μm.

[0085] To prepare various types of aluminum-based composite materials, multiple types of raw material powders were generated. The corresponding matrix phase powder and reinforcing phase powder for each type were mixed and ball-milled to obtain the corresponding raw material powder. The ball milling speed was 250 rpm, the ball-to-powder ratio was 15:1, and the milling time was 10 hours.

[0086] 2) Brush silicon carbide onto the inner wall of the prepared mold, and then... Figure 1 The hexagonal aluminum honeycomb structure shown is placed in the mold, and then the different types of raw material powder prepared in step 1) are filled into the different cavities one by one to obtain honeycomb structures filled with different types of raw material powder. Take a graphite block with a diameter 1-2 mm larger than the mold cavity and a thickness of 20 mm, and place it on both sides of the mold.

[0087] 3) At room temperature, cold pressing is performed. A cold press is used to press the graphite block into the mold cavity at a pressure of 5t for 30s. The honeycomb structure containing different types of raw material powder is cold pressed to form a honeycomb blank.

[0088] 4) Place the mold containing the honeycomb ingot into a vacuum hot press furnace. First, heat to 673K ​​and hold for 1.5 hours to remove stearic acid. Then, heat to 813K and hold for 1 hour, followed by hot pressing until dense. After the pressure is increased to 20t, hold at that temperature for 30 minutes, and then cool down with the furnace. After removing the mold, the honeycomb ingot is obtained.

[0089] 5) Take a 6061Al block with a thickness of 12-13mm and a diameter 2-3mm smaller than the honeycomb ingot. Weld the 6061Al block to one end of the honeycomb ingot. Hot-extrude the honeycomb ingot into honeycomb rods at 723K along the hot-pressing direction with an extrusion ratio of 16:1.

[0090] 6) The bar is solution treated at 773K for 2 hours, then quenched in water and aged naturally for more than 96 hours to obtain a honeycomb aluminum matrix composite material; wherein, the honeycomb aluminum matrix composite material includes various types of aluminum matrix composite material units, and the aluminum matrix composite material units correspond one-to-one with the honeycomb units.

[0091] The microstructure diagram of the honeycomb aluminum matrix composite material obtained in this embodiment is shown below. Figure 6 As shown; the light-colored elements represent hexagonal aluminum honeycomb structures, while the dark-colored elements represent different aluminum-based composite material units. From Figure 6 As can be seen, the hexagonal aluminum honeycomb structure remains intact and undamaged. The honeycomb structure effectively separates different types of aluminum-based composite materials.

[0092] Comparative Example 1

[0093] Comparative Example 1 provides a high-throughput preparation method for aluminum-based composite materials, which can prepare multiple aluminum-based composite materials in one step, and subsequently perform high-throughput characterization of the prepared materials. Details are as follows:

[0094] 1) Design of Aluminum-Based Composite Materials: The aluminum matrix for the aluminum-based composite materials to be screened includes pure aluminum, 5052Al (aluminum alloy of type 5052Al), 5056Al (aluminum alloy of type 5056Al), 6063Al (aluminum alloy of type 6063Al), and 7075Al (aluminum alloy of type 7075Al). The reinforcing phases include Al2O3, TiC, B4C, and CNTs, with a reinforcing phase content of 1-6 vol%, in 1 vol% increments. For simplicity, the designed aluminum-based composite material is represented as A+B(C). Here, A represents the matrix type, B represents the reinforcing type, and C represents the reinforcing phase content (vol%). Specifically, the type of aluminum-based composite material designed in this embodiment (the aluminum-based composite material to be prepared) is as follows:

[0095] 5052Al+SiC (1vol%), 5052Al+SiC (2vol%), 5052Al+SiC (3vol%), 5052Al+SiC (4vol%), 5052Al+SiC (5vol%), 5056Al+Al2O3 ( 1vol%), 5056Al+Al2O3 (2vol%), 5056Al+Al2O3 (3vol%), 5056Al+Al2O3 (4vol%), 5056Al+Al2O3 (5vol%), 5056Al+Al2O3 (6vol %), 6063Al+B4C (1vol%), 6063Al+B4C (2vol%), 6063Al+B4C (3vol%), 6063Al+B4C (4vol%), 6063Al+B4C (5vol%), 7075Al+CNT s(1vol%), 7075Al+CNTs(2vol%), 7075Al+CNTs(3vol%), 7075Al+CNTs(4vol%), 7075Al+CNTs(5vol%), 7075Al+CNTs(6vol%).

[0096] The required raw materials are as follows: Al2O3 powder with an average particle size of 10 μm; SiC powder with an average particle size of 10 μm; B4C powder with an average particle size of 10 μm; CNTs with an average particle size of 10 nm and a length of approximately 5 μm; 5052Al with an average particle size of 10 μm; 5056Al powder with an average particle size of 10 μm; 6063Al powder with an average particle size of 80 μm; and 7075Al powder with an average particle size of 79.5 μm.

[0097] To prepare various types of aluminum-based composite materials, multiple types of raw material powders were generated. The corresponding matrix phase powder and reinforcing phase powder for each type were mixed and ball-milled to obtain the corresponding raw material powder. The ball milling speed was 250 rpm, the ball-to-powder ratio was 15:1, and the milling time was 10 hours.

[0098] 2): Brush silicon carbide onto the inner wall of the prepared mold, and then... Figure 1 The hexagonal aluminum honeycomb structure shown is placed in the mold, and then the different types of raw material powder prepared in step 1) are filled into the different cavities one by one to obtain honeycomb structures filled with different types of raw material powder. Take a graphite block with a diameter 1-2 mm larger than the mold cavity and a thickness of 20 mm, and place it on both sides of the mold.

[0099] 3) At room temperature, cold pressing is performed. A cold press is used to press the graphite block into the mold cavity at a pressure of 5t for 30s. The honeycomb structure containing different types of raw material powder is cold pressed to form a honeycomb blank.

[0100] 4) Place the mold containing the honeycomb ingot into a vacuum hot press furnace. First, heat to 673K ​​and hold for 1.5 hours to remove stearic acid. Then, heat to 813K and hold for 1 hour, followed by hot pressing until dense. After the pressure is increased to 20t, hold at that temperature for 30 minutes, and then cool down with the furnace. After removing the mold, the honeycomb ingot is obtained.

[0101] 5) The billet is solution treated at 773K for 2 hours, then quenched in water and naturally aged for more than 96 hours to obtain a honeycomb aluminum matrix composite material; wherein, the honeycomb aluminum matrix composite material includes various types of aluminum matrix composite material units, and the aluminum matrix composite material units correspond one-to-one with the honeycomb units.

[0102] The microstructure of the honeycomb aluminum matrix composite material obtained in Comparative Example 1 is shown in the figure below. Figure 7 As shown; the ingot size after hot pressing is large, so it is impossible to show all the composite materials under a scanning electron microscope; the bright colors represent hexagonal aluminum honeycomb structures, and the dark colors represent different aluminum-based composite material units. From Figure 7 As can be seen, the hexagonal aluminum honeycomb composite material exhibits numerous pores after hot pressing, indicating that the composite material, which only undergoes hot pressing and sintering without hot extrusion, has defects. The hot pressing and sintering steps, along with the hot extrusion steps, have a synergistic effect in improving the material's density.

[0103] In summary, this invention provides a high-throughput preparation method for aluminum-based composite materials. Using a hexagonal aluminum honeycomb structure as a framework and hexagonal cell structures (i.e., accommodating cavities) as screening points, the method is fabricated using powder metallurgy. The hexagonal aluminum honeycomb structure isolates different aluminum-based composite material units, while the hexagonal cell structures serve as screening points for preparing different types and contents of aluminum-based composite materials. This high-throughput preparation method allows for the simultaneous preparation of multiple types of aluminum-based composite material units. Therefore, this invention holds promise as a highly efficient technology for screening the types and contents of reinforcing phases in composite materials.

[0104] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention shall still fall within the scope of the technical solution of the present invention.

Claims

1. A high-throughput preparation method for aluminum-based composite materials, characterized in that, It includes the following steps: Raw material preparation: Prepare various types of raw material powders; each type of raw material powder includes aluminum matrix powder and reinforcing phase; Prepare a honeycomb structure: Prepare a honeycomb structure with multiple accommodating cavities. The honeycomb structure is a hexagonal honeycomb structure made of aluminum. The accommodating cavities on the honeycomb structure are open at both ends. Different types of raw material powders are filled into different accommodating cavities one by one to obtain honeycomb structures filled with different types of raw material powders. Cold pressing: The honeycomb structure containing different types of raw material powder is cold pressed to obtain a honeycomb blank; Hot pressing: The honeycomb-shaped billet is subjected to vacuum hot pressing to obtain a honeycomb-shaped ingot; Hot extrusion treatment: The Al alloy block is welded to one end of the honeycomb billet, and then the honeycomb billet is hot extruded in the direction of hot pressing to extrude the honeycomb billet into a honeycomb extruded structure; the temperature of hot extrusion treatment is 723-823K, and the extrusion ratio is (4-16):1; the honeycomb extruded structure is a rod. Heat treatment: The honeycomb extrusion structure is heat treated to obtain a rod-shaped honeycomb aluminum matrix composite material; wherein, the honeycomb aluminum matrix composite material includes various types of aluminum matrix composite material units and honeycomb structures; the aluminum hexagonal honeycomb structure serves as a framework, which deforms in coordination with the material throughout the entire preparation process without being destroyed, and is completely preserved in the final honeycomb aluminum matrix composite material rod; different aluminum matrix composite material units are isolated from each other by the honeycomb structure.

2. The high-throughput preparation method of aluminum-based composite materials according to claim 1, characterized in that, In the step of preparing raw materials: The aluminum matrix powder is selected from aluminum powder or aluminum alloy powder; The reinforcing phase is selected from ceramic phase and / or carbon materials.

3. The high-throughput preparation method of aluminum-based composite materials according to claim 2, characterized in that, The reinforcing phase is selected from one or more of alumina, silicon carbide, boron carbide, and carbon nanotubes.

4. The high-throughput preparation method of aluminum-based composite materials according to any one of claims 1-3, characterized in that, In the step of preparing raw materials: In each type of raw material powder, the content of the reinforcing phase is 0.5-30 vol.

5. The high-throughput preparation method of aluminum-based composite materials according to any one of claims 1-3, characterized in that, In the step of preparing raw materials: When preparing each type of raw material powder, the aluminum matrix powder and the reinforcing phase are placed in a ball mill and ball milled under an inert atmosphere.

6. The high-throughput preparation method of aluminum-based composite materials according to claim 5, characterized in that, The ball milling speed is 100-400 rpm, the ball powder ratio is (5-15):1, and the ball milling time is 5-15 h; Stearic acid needs to be added during ball milling to prevent the raw material powder from sintering.

7. The high-throughput preparation method of aluminum-based composite materials according to any one of claims 1-3, characterized in that, Prepare a mold for cold pressing and hot pressing. Place a first graphite block at the bottom of the mold, place the honeycomb structure on the graphite block, and then fill different types of raw material powders into different accommodating cavities one by one. Seal the mold with a second graphite block, and then perform cold pressing and hot pressing in sequence. After hot pressing, the mold and graphite block are removed.

8. The high-throughput preparation method of aluminum-based composite materials according to claim 7, characterized in that, Before placing the honeycomb structure into the mold, silicon carbide needs to be brushed onto the inner wall of the mold.

9. The high-throughput preparation method of aluminum-based composite materials according to any one of claims 1-3, characterized in that, In the cold pressing step: Set the pressure of the cold press to 3-5t and the pressure holding time to 5-30s.

10. The high-throughput preparation method of aluminum-based composite materials according to any one of claims 1-3, characterized in that, In the hot pressing process: In a vacuum hot press furnace, the stearic acid in the honeycomb blank is first removed by heating, and then hot pressing is performed. After the hot pressing is completed, the furnace is cooled down. The temperature for removing stearic acid from the honeycomb preform is 673-723K, and the holding time is 1-2h.

11. The high-throughput preparation method of aluminum-based composite materials according to claim 10, characterized in that, The hot pressing temperature is 813-903K. After holding the hot pressing temperature for 1-2 hours, the pressure is increased to 15-20t and held for 30-60 minutes.

12. The high-throughput preparation method of aluminum-based composite materials according to any one of claims 1-3, characterized in that, In the thermal extrusion process: The Al alloy block is a 6061Al alloy block.

13. The high-throughput preparation method of aluminum-based composite materials according to any one of claims 1-3, characterized in that, In the heat treatment step: The honeycomb extruded structure is subjected to solution treatment, quenching, and natural aging in sequence to obtain a honeycomb aluminum matrix composite material; The solution treatment is performed at a temperature of 723-873K for 2-5 hours. The quenching is carried out in water; The natural shelf life is 96 hours or more.

14. A honeycomb aluminum-based composite material, characterized in that, The honeycomb aluminum matrix composite material includes various types of aluminum matrix composite material units and an aluminum hexagonal honeycomb structure; the aluminum hexagonal honeycomb structure is completely preserved in the honeycomb aluminum matrix composite material rod, and different aluminum matrix composite material units are isolated from each other by the aluminum hexagonal honeycomb structure; the aluminum matrix composite material is prepared by the high-throughput preparation method of the aluminum matrix composite material according to any one of claims 1-13.

Citation Information

Patent Citations

  • Combined material hot isostatic pressing high-flux micro-manufacturing method and sheathing die thereof

    CN109759594A